2014
DOI: 10.5812/thrita.16607
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Coenzyme Q10 in Chronic Constriction Injury-Induced Neuropathic Pain in Rat

Abstract: Background: Oxidative stress contributes to neuropathic pain. Coenzyme Q10 (CoQ10) is used for the treatment of neurodegenerative diseases. However, there is no report regarding the therapeutic effect of CoQ10 on neuropathic pain. Objectives: The present study investigated the effects of CoQ10 on pain alleviation in animals with chronic constriction injury (CCI) of the sciatic nerve. Materials and Methods: Wistar male rats were randomly allocated to four groups. Nerve injury was induced by four loose ligatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Nissl staining was used to distinguish healthy neurons from dead neurons [62]. Mason Trichrome Staining (MTS) was used for selective differentiation visualization of collagen fibers, according to the usual protocol [63].…”
Section: Histological Studymentioning
confidence: 99%
“…Nissl staining was used to distinguish healthy neurons from dead neurons [62]. Mason Trichrome Staining (MTS) was used for selective differentiation visualization of collagen fibers, according to the usual protocol [63].…”
Section: Histological Studymentioning
confidence: 99%
“…11 However, in our study, the histomorphological evaluation of the eighth-week groups was superior to the fourth-week groups. Janzade et al 12 evaluated the thermal plantar test and histomorphological assessment in their experimental study with rats, and they showed that the treatment group, which received coenzyme Q10, had superior results according to these evaluations. In our study, we found that the myelin structures, the number of myelinated axon fibers, and the morphological evaluation of organelles were significantly better in the treatment groups than in the control groups ( P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effect of coenzyme 10 has already been demonstrated in previous studies using either intraperitoneal or parenteral routes. 11 , 12 To our knowledge, there are no reported studies in the English literatur on the effects of local use of coenzyme Q10 and vitamin E combination derivatives in peripheral nerve injury. In our study, the clinical, electrophysiological, and histomorphological effects of local coenzyme Q10 and vitamin E use in peripheral nerve injury were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the positive effect of antioxidants on the enhancement of nerve regeneration is the focus of attention [66]. As stated previously, CoQ10 is a well-known antioxidant with bioenergetic, antiinflammatory, and neuroprotective properties [67]. In the acute inflammatory phase of sciatic nerve injury, intraperitoneal injection of 10 mg/kg per day was observed to enhance nerve regeneration [68].…”
Section: Effects Of Coq10 On the Regeneration Of Peripheral Nerve Injurymentioning
confidence: 97%